Ethiopia Regional Poverty Report : Promoting Equitable Growth for All Regions - World Bank (World Bank, Washington, DC, 2020)
Ethiopia’s economy has grown rapidly over the last two decades, leading to significant national poverty reduction, but there were significant differences in the pace and nature of poverty reduction across Ethiopia’s eleven regions. Based on the national poverty line, poverty decreased from 46 percent in 1996 to 24 percent in 2016 nationwide. Poverty decreased in all the regions, particularly after 2005 when growth became more robust. Although regional disparities remained fairly low, regional poverty rates converged until 2011 only to begin diverging again in 2016.